The impact of COVID-19 pandemic on orthodontic services and trainees’ mental health in India - Thiruvenkatachari, Badri; Sivakumar, Prema; Ananth, Sanjana; Sabbagh, Yana; Lewis, Benjamin R. K.; Chadwick, Stephen M.; Kaliyaperumal, Gnana Shanmugam; Batra, Panchali (Frontiers in Medicine, 2023)
Aim To evaluate the impact of COVID-19 on clinical orthodontic services, orthodontic education, and the emotional well-being of orthodontists and orthodontic trainees in India. Materials and methods The survey was designed using Survey Monkey™ and distributed to members of the Indian Orthodontic Society via their registered email address and also via social media platforms (WhatsApp and LinkedIn). Results A total of 610 responses to the survey were received. The majority of respondents agreed on the negative impact of COVID-19 on clinical activity and the associated income of orthodontists. Respondents reported that this was mainly due to national restrictions (70.1%), increased cross infection measures (59.6%), state restrictions (55.9%), and social distancing (39.4%). Ninety one percent of respondents agreed that orthodontic staff should have evidence of vaccination before providing care. COVID-19 was found to have a negative impact on the trainees’ perceptions of their clinical dexterity (72.4%), their confidence with respect to academic knowledge (66.5%), their mental health (80.7%), and their stress levels during the pandemic (93.2%). Conclusion The COVID-19 pandemic has had a negative impact on orthodontic specialists and post-graduate trainees in India. The impact on trainees’ mental health was significantly higher compared to trainees from other countries. Decreased clinical activity has reduced the opportunities for learning, and trainers must rise to the challenge of providing additional support to this cohort of trainees who will progress to become the future orthodontic workforce.